Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To find the equation of the line tangent to the graph of [tex]\( f(x) = -2x^3 \)[/tex] at the point [tex]\((-1, 2)\)[/tex], we will follow a step-by-step procedure involving the calculation of the derivative, the slope at the point of tangency, and then using the point-slope form of the equation of a line.
1. Determine the function and the point of tangency:
- The function is [tex]\( f(x) = -2x^3 \)[/tex].
- The point of tangency is [tex]\((-1, 2)\)[/tex].
2. Find the derivative of [tex]\( f(x) \)[/tex]:
- To find the slope of the tangent line, we need the derivative of [tex]\( f(x) \)[/tex]. The derivative [tex]\( f'(x) \)[/tex] is given by:
[tex]\[ f'(x) = \frac{d}{dx} (-2x^3) = -6x^2 \][/tex]
3. Evaluate the derivative at the point of tangency (i.e., find the slope):
- The slope of the tangent line at [tex]\((-1, 2)\)[/tex] is given by [tex]\( f'(-1) \)[/tex]:
[tex]\[ f'(-1) = -6(-1)^2 = -6(-1) = -6 \][/tex]
- Therefore, the slope of the tangent line is [tex]\(-6\)[/tex].
4. Use the point-slope form of the equation of a line to find the tangent line:
- The point-slope form of the equation of a line is:
[tex]\[ y - y_1 = m(x - x_1) \][/tex]
where [tex]\( m \)[/tex] is the slope, and [tex]\((x_1, y_1)\)[/tex] is the point of tangency.
- Substituting the values [tex]\( x_1 = -1 \)[/tex], [tex]\( y_1 = 2 \)[/tex], and [tex]\( m = -6 \)[/tex] into the equation, we have:
[tex]\[ y - 2 = -6(x - (-1)) \][/tex]
- Simplifying the equation:
[tex]\[ y - 2 = -6(x + 1) \][/tex]
[tex]\[ y - 2 = -6x - 6 \][/tex]
[tex]\[ y = -6x - 6 + 2 \][/tex]
[tex]\[ y = -6x - 4 \][/tex]
Therefore, the equation of the tangent line at the point [tex]\((-1, 2)\)[/tex] is:
[tex]\[ y = -6x - 4 \][/tex]
So, in the question formatting style:
The equation of the tangent line is [tex]\( y = -6x - 4 \)[/tex].
1. Determine the function and the point of tangency:
- The function is [tex]\( f(x) = -2x^3 \)[/tex].
- The point of tangency is [tex]\((-1, 2)\)[/tex].
2. Find the derivative of [tex]\( f(x) \)[/tex]:
- To find the slope of the tangent line, we need the derivative of [tex]\( f(x) \)[/tex]. The derivative [tex]\( f'(x) \)[/tex] is given by:
[tex]\[ f'(x) = \frac{d}{dx} (-2x^3) = -6x^2 \][/tex]
3. Evaluate the derivative at the point of tangency (i.e., find the slope):
- The slope of the tangent line at [tex]\((-1, 2)\)[/tex] is given by [tex]\( f'(-1) \)[/tex]:
[tex]\[ f'(-1) = -6(-1)^2 = -6(-1) = -6 \][/tex]
- Therefore, the slope of the tangent line is [tex]\(-6\)[/tex].
4. Use the point-slope form of the equation of a line to find the tangent line:
- The point-slope form of the equation of a line is:
[tex]\[ y - y_1 = m(x - x_1) \][/tex]
where [tex]\( m \)[/tex] is the slope, and [tex]\((x_1, y_1)\)[/tex] is the point of tangency.
- Substituting the values [tex]\( x_1 = -1 \)[/tex], [tex]\( y_1 = 2 \)[/tex], and [tex]\( m = -6 \)[/tex] into the equation, we have:
[tex]\[ y - 2 = -6(x - (-1)) \][/tex]
- Simplifying the equation:
[tex]\[ y - 2 = -6(x + 1) \][/tex]
[tex]\[ y - 2 = -6x - 6 \][/tex]
[tex]\[ y = -6x - 6 + 2 \][/tex]
[tex]\[ y = -6x - 4 \][/tex]
Therefore, the equation of the tangent line at the point [tex]\((-1, 2)\)[/tex] is:
[tex]\[ y = -6x - 4 \][/tex]
So, in the question formatting style:
The equation of the tangent line is [tex]\( y = -6x - 4 \)[/tex].
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.